Analisis Desain Sistem Informasi Perpustakaan Berbasis QR Code dan Notifikasi Otomatis - Nazwa Kafka Nafiza; Heru Sutejo; Siti Fatima Wagab; Ella Natalia Kogoya; Anggi Sukmawati (Tamilis Synex: Multidimensional Collaboration, 2026)
Library management at SMK Negeri 2 Bisnis Manajemen Jayapura is still conducted manually, resulting in several challenges, including slow transaction recording processes, difficulties in data retrieval, and the absence of an [1] Automatic Notification system for book returns. This study aims to design a [6] Web-Based Library System integrated with [2] QR Code technology and automatic notifications. The research employed a descriptive qualitative approach with a Research and Development (R&D) methodology. System development was conducted using the [3] SDLC Waterfall model and was limited to the [4] System Design stage. Data were collected through observation, interviews, and documentation studies. The results of this study consist of a system design that includes requirements analysis and [5] UML modeling comprising Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Entity Relationship Diagrams (ERD), as well as user interface design. The proposed system integrates QR Codes as unique book identifiers and automatic notifications as book return reminders. The resulting design is expected to serve as a foundation for the future development and implementation of a more effective and structured digital library system